Vacuolated Leukocytes in the Peripheral Blood Smear of a Child with Chanarin-Dorfman Syndrome - Akyay, Arzu; Sahin, Filiz Demir; Sen, Askin (Galenos Yayincilik, 2020)
[Abstract Not Available]
Chanarin-dorfman sendromlu bir çocukta periferik yaymada vakuollü lökositler
Keywords: Chanarin-Dorfman Syndrome; Vacuolated leukocytes